Penentuan Koefisien Atenuasi Radiasi Gamma pada Bahan Cobalt-60 dengan Menggunakan Material Alternatif Non-Logam Sebagai Shielding. - Maritza Arisatya Wijaya; Sovian Aritonang (Fakultas Teknik UMSU, 2026)
Gamma radiation emitted by the Cobalt-60 (⁶⁰Co) isotope is a high-energy ionizing radiation source widely employed in various applications. The gamma photons produced, with energies ranging from 1.17 MeV to 1.33 MeV, possess a high penetrating capability; consequently, the selection of an appropriate shielding material is critical to ensuring radiation safety and protection. Previous experimental studies have largely focused on lead (Pb) as the primary shielding material, which is nevertheless limited by its toxicity and the relatively high cost of its handling and disposal, thereby motivating the search for safer and more economical alternatives. However, systematic comparisons of the shielding effectiveness of several candidate materials against ⁶⁰Co gamma radiation under controlled thickness and testing conditions remain limited. This study therefore aims to determine and compare the Linear Attenuation Coefficient (LAC) of several selected materials and to evaluate their effectiveness as gamma radiation shields. The method employed involves experimental measurement of radiation intensity using a calibrated detector after transmission through samples of varying material composition; the resulting data are subsequently analyzed using the Beer–Lambert law to calculate the attenuation coefficient of each material.